(untitled) (Journal of Management and Social Sciences, 2018)
Border is one of the most visible signs of the sovereignty of a state on its territory. In spite of the resilient efforts of Nigeriaâ€™s border security agencies to ensure the safeguarding of Nigeria’s territorial sovereignty, smuggling remains unabated and its dynamics is characterised with strong link between the smugglers and itineraries. The main objective of this paper is to examine the socio-economic effects of smuggling of food commodities from Republic of Benin to Nigeria through Okerete borderland route, Saki. The methodology used for the paper involves descriptive survey design while interviews were conducted among the patrol teams of custom officers in Saki, and secondary sources such as journal article, internet materials and current situation in the country serves as sources of data collections. The paper concluded that the spate of smuggling of foods commodities mostly rice and frozen foods across Saki borderlands has undermined income generation, rule of law, social vices in the communities, uncontrolled market economy and price fluctuation of commodity like rice and vegetable oil, health deterioration from these substances, and encourage drop-out (child abuse) in these communities. Keywords Border, smuggling, food commodity, border management